Transmethodology: : Creating spaces for transgressive and transformative inquiry - Kousholt, Dorte; Khawaja, Iram (Outlines. Critical Practice Studies, 2023)
The special issue deals with entanglements, borders, and bridges between ideas, concepts, and spheres often considered separate and distinct elements in research processes that are frequently represented as well-ordered and linear. Under the heading transmethodology, our aim has been to make space for and bring to light the often messy, non-linear, and complex research processes that form our methodologies.